Effect of Cordyceps militaris extract containing cordycepin on the adipogenesis and lipolysis of adipocytes - Kazuya Kusama; Kodai Oka; Yumi Yashiro; Kanoko Yoshida; Hiroaki Miyaoka; Kazuhiro Tamura (FEBS Open Bio)
Obesity, a global health concern, results from an energy imbalance leading to lipid accumulation. In the present study, Cordyceps militaris extract (CM) and its primary component, cordycepin, were investigated to characterize their potential effects on adipogenesis and lipolysis. Treatment with CM or cordycepin reduced lipid droplets and increased hormone‐sensitive lipase activation in 3T3‐L1 cells. In a diabetic obese mouse model, CM and cordycepin lowered serum low‐density lipoprotein/very low‐density lipoprotein levels and reduced oxidative stress and cell senescence markers. Thus, cordycepin inhibits preadipocyte differentiation and promotes lipolysis, which may serve as a novel obesity treatment. Further studies, including clinical trials, are required to validate the clinical potential of cordycepin.